Reaksi Pasar pada Pengumuman Dividen dengan Profitabilitas sebagai Pemoderasi di BEI - Larimanu, Ina Intan Dortianti; Suaryana, I Gusti Ngurah Agung (E-Jurnal Akuntansi; Vol 12 No 3 (2015), 2016)
This research was conducted with the aim of knowing the market reaction which occurs during the announcement of a cash dividend to profitability as moderating in the Indonesia Stock Exchange (IDX), where profitability is measured as return on assets. The sample in this study 699 companies that announced a cash dividend and 123 companies that meet the criteria sampling. Data analysis using moderate regression analysis. The results of the analysis concludes that the market reacted positively to the announcement of dividends and profitability weakened the market reaction to the announcement of the dividend on the company listed in Indonesia Stock Exchange (IDX).
Keywords: market reaction; dividend announcement; return on assets